Astrobiology and Society: Building an Interdisciplinary Research Community - Race, Margaret (Mary Ann Liebert, Inc., 2012)
This paper reports recent efforts to gather experts from the humanities and social sciences along with astrobiologists to consider the cultural, societal, and psychological implications of astrobiology research and exploration. We began by convening a workshop to draft a research roadmap on astrobiology's societal implications and later formed a Focus Group on Astrobiology and Society under the auspices of the NASA Astrobiology Institute (NAI). Just as the Astrobiology Science Roadmap and various astrobiology science focus groups have helped researchers orient and understand their work across disciplinary contexts, our intent was to apply the same approach to examine areas beyond the physical and life sciences and expand interdisciplinary interaction and scholarly understanding. These efforts continue as an experiment in progress, with an open invitation to interested researchers—astrobiologists as well as scholars in the humanities and social sciences—to become involved in research, analysis, and proactive discussions concerning the potential impacts of astrobiology on society as well as the possible impacts of society on progress in astrobiology. Key Words: Astrobiology—Extraterrestrial life—Life detection. Astrobiology 12, 958–965.